2018
DOI: 10.1021/acs.analchem.8b02839
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Screening and Identification of Fatty Acid Esters of Hydroxy Fatty Acids in Plant Tissues by Chemical Isotope Labeling-Assisted Liquid Chromatography–Mass Spectrometry

Abstract: Fatty acid esters of hydroxy fatty acids (FAHFAs) are a new class of lipid mediators with promising anti-diabetic and anti-inflammatory properties. Comprehensive screening and identification of FAHFAs in biological samples would be beneficial to the discovery of new FAHFAs and enable greater understanding of their biological functions. Here, we report the comprehensive screening of FAHFAs in rice and  Arabidopsis thaliana by chemical isotope labeling-assisted liquid chromatography-mass spectrometry (CIL-LC-MS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 24 publications
0
80
0
Order By: Relevance
“…Our laboratory discovered a class of structurally novel bioactive lipids, branched fatty acid esters of hydroxy fatty acids (FAHFAs), that are synthesized in humans, animals, and plants, and have antidiabetic and antiinflammatory properties (13)(14)(15). FAHFAs consist of a fatty acid and a hydroxy fatty acid linked by an ester bond.…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory discovered a class of structurally novel bioactive lipids, branched fatty acid esters of hydroxy fatty acids (FAHFAs), that are synthesized in humans, animals, and plants, and have antidiabetic and antiinflammatory properties (13)(14)(15). FAHFAs consist of a fatty acid and a hydroxy fatty acid linked by an ester bond.…”
Section: Introductionmentioning
confidence: 99%
“…The LC-MS protocol used by Pflimlin et al to measure PAHSA levels did not recapitulate any of the protocols published by three independent groups (Brezinova et al, 2018; Kolar et al, 2018; Kuda et al, 2018; Ma et al, 2015; Syed et al, 2018; Zhang et al, 2016; Yore et al, 2014) (Table S2) or more recently by an additional group (Zhu et al, 2018). Furthermore, no information is provided comparing their protocol to any of the reported procedures to validate their results.…”
Section: Lc-msmentioning
confidence: 92%
“…An in silico analysis predicted that >1,000 FAHFAs could exist in nature (Ma et al, 2015), and >20 FAHFA families have been identified in mammalian tissues (Kuda et al, 2016, 2018; Ma et al, 2015; Yore et al, 2014), with many additional families in plants (Zhu et al, 2018). These families differ by their acyl-chain composition and consist of multiple isomers distinguished by the position of the ester bond between acyl chains.…”
mentioning
confidence: 99%
“…The results indicated that twin derivatization-based LC-MS provided a more accurate view of global FFAs and had great application potential in the fields of targeted metabolomics. Zhu et al developed a comprehensive screening and identification strategy of fatty acid esters of hydroxy fatty acids (FAHFA) in plant tissues by LC-MS using commercial 2-dimethylaminoethlamine and synthesized d 4 -2-dimethylaminoethlamine as isotope labeling derivatization reagents [48]. They detected 49 potential FAHFA families, including 262 regioisomers, in tissues of rice and Arabidopsis thaliana.…”
Section: Lc-ms-based Derivatization Approaches For Fas and Oxylipinsmentioning
confidence: 99%